An Update in Qualitative Imaging of Bone Using Ultrashort Echo Time Magnetic Resonance - Jerban, Saeed; Chang, Douglas G.; Ma, Yajun; Jang, Hyungseok; Chang, Eric Y.; Du, Jiang (Frontiers in Endocrinology, 2020)
Bone is a composite material comprised of mineral, organic matrix and water. X-ray-based techniques are the standard approach for bone evaluation in clinics, but they are unable to detect the organic matrix and water components in bone. Magnetic resonance imaging (MRI) is being used increasingly for bone evaluation. While MRI can non-invasively assess the proton pools in soft tissues, cortical bone typically appears as a signal void with clinical MR techniques because of its short T2*. New MRI techniques have been recently developed to image bone while avoiding the ionizing radiation present in x-ray-based methods. Qualitative bone imaging can be achieved using ultrashort echo time (UTE), single inversion recovery UTE (IR-UTE), dual-inversion recovery UTE (Dual-IR-UTE), double-inversion recovery UTE (Double-IR-UTE), and zero echo time (ZTE) sequences. The contrast mechanisms as well as the advantages and disadvantages of each technique are discussed.